2015
DOI: 10.1536/ihj.14-374
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Left Atrial Appendage Morphology Evaluated by Trans-Esophageal Echocardiography and Ischemic Cerebral Stroke in Patients With Atrial Fibrillation

Abstract: SummaryThe left atrial appendage (LAA) represents one of the major sources of cardiac thrombi responsible for embolic stroke in patients with atrial fibrillation (AF). The aim of the present study was to evaluate LAA structure and functions by transesophageal echocardiography (TEE) in patients with AF to investigate the possible association between the different LAA morphologies and the patients' history of ischemic cerebral stroke. We included 50 patients with non-valvular AF (29 chronic, 21 paroxysmal), 24 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Previous echocardiographic studies compared morphologic parameters of LAA and LAAT, and suggested that left atrium/LAA enlargements contributed to LAAT formation. [14][15][16] Consistent with previous reports, we found that left atrial volume, LAA orifice dimension, LAA depth, and LAA flow velocity were associated with LAAT. However, histological evidence has been absent regarding this issue.…”
Section: Clinical and Histological Factors Associated With Laatsupporting
confidence: 91%
“…Previous echocardiographic studies compared morphologic parameters of LAA and LAAT, and suggested that left atrium/LAA enlargements contributed to LAAT formation. [14][15][16] Consistent with previous reports, we found that left atrial volume, LAA orifice dimension, LAA depth, and LAA flow velocity were associated with LAAT. However, histological evidence has been absent regarding this issue.…”
Section: Clinical and Histological Factors Associated With Laatsupporting
confidence: 91%
“…One possible mechanism behind may be that the incidence of thrombi formation in LAA with different anatomical characteristics, i.e., LAA morphology and number of LAA lobes, varied. Now it is recognized that there were four LAA macroscopic morphologies, including cactus LAA, chicken wing LAA, windsock LAA and cauliflower LAA [ 5 , 16 21 ]. Several recent studies have demonstrated that different LAA morphologies obtained by Cardiac CT or MRI are closely correlated with LASEC, transient ischaemic attacks (TIA) and strokes in patients with AF [ 16 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Now it is recognized that there were four LAA macroscopic morphologies, including cactus LAA, chicken wing LAA, windsock LAA and cauliflower LAA [ 5 , 16 21 ]. Several recent studies have demonstrated that different LAA morphologies obtained by Cardiac CT or MRI are closely correlated with LASEC, transient ischaemic attacks (TIA) and strokes in patients with AF [ 16 21 ]. However, the relationship between LAA lobes and markers of thromboembolic risk (decreased LAA flow velocity, LASEC, LA thrombus) has not been fully characterized in patients with NVAF.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several morphological and functional abnormalities including LAA orifice area, LAA depth, LAA volume and LAA flow velocity have been studied in several observational studies. [19][20][21][22][23][24] It has been shown that the increase in LAA orifice area, depth and volume and decrease in LAA velocity are strongly associated with increased stroke risk in AF. [19][20][21][22][23][24] These changes are attributable to blood pooling and stasis triggered by AF itself.…”
Section: Figurementioning
confidence: 99%
“…[19][20][21][22][23][24] It has been shown that the increase in LAA orifice area, depth and volume and decrease in LAA velocity are strongly associated with increased stroke risk in AF. [19][20][21][22][23][24] These changes are attributable to blood pooling and stasis triggered by AF itself. Therefore, a systematic review and meta-analysis of all studies that address these parameters should be done in order to demonstrate the final association between these variables and the risk of embolic stroke and try to find a cut-off values that could help in assessing the risk of thromboembolism in AF patients.…”
Section: Figurementioning
confidence: 99%